Hesperetin Promotes Cisplatin−Induced Apoptosis of Gastric Cancer In Vitro and In Vivo by Upregulating PTEN Expression - He, Pengzhan; Ma, Jingjing; Liu, Yinghui; Deng, Huan; Dong, Weiguo (Frontiers in Pharmacology, 2020)
As one of the most common malignant gastrointestinal tumors, gastric cancer (GC) has a high incidence and poor prognosis. Cisplatin (DDP) is often used as chemotherapy for advanced GC; however, the high incidence of drug resistance remains a problem. The use of several anti-tumor drugs as combined chemotherapy is an effective strategy. Hesperetin has anti-tumor ability via its pro-apoptotic effect on various human cancers, both in vitro and in vivo, with no significant toxicity. However, a combination of DDP and hesperetin in GC has not been reported. The present study aimed to investigate the in vitro and in vivo chemosensitization effect and mechanism of hesperetin-augmented DDP-induced apoptosis of GC. The proliferation of GC ty -60cells was inhibited significantly in a time and dose-dependent manner by combined treatment of DDP with hesperetin. Hesperetin markedly increased DDP-induced apoptosis of GC cell lines. In a xenograft tumor mouse model, markedly better tumor suppression was observed after treatment with DDP plus hesperetin compared with that of either agent alone. Additionally, the combination of DDP and hesperetin remarkably increased the expression levels of phosphatase and tensin homolog (PTEN) and Cytochrome C (Cyt C), and significantly decreased the levels of phosphorylated protein kinase B (p-AKT) and CyclinD1. DDP and hesperetin also induced significant increases in apoptosis inducing factor (AIF), BCL2 associated X, apoptosis regulator (BAX), cleaved caspase-9, and cleaved caspase-3, and decreased B-cell lymphoma 2 (BCL2), caspase-9, and caspase-3 levels. Thus, we demonstrated that hesperetin could inhibit the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/AKT signaling pathway and induce the mitochondrial pathway via upregulating PTEN expression, thereby significantly enhancing DDP’s anti-tumor effect on GC. Hesperetin is a potential chemotherapeutic agent for GC and merits further clinical investigation.